Angola, RDC e Ruanda na confluência da (in)estabilidade do Interland Africano - Almeida, E. C. (IV Congresso Internacional de Angolanística, 2025)
Abstract: The situation in the Great Lakes region stems from two major factors: i) the ethnic crisis between the Hutu and Tutsi peoples in Burundi and Rwanda, and Rwanda's civil war between 1990 and 1994, which culminated in one of history’s most tragic events: the genocide of approximately 800,000 Rwandans within the first 100 days of the conflict; and ii) the two Congo Wars (1996–1997 and 1998–2003). Both Angola and Rwanda participated in these two significant wars in Zaire/DRC. In the Second War—also known as the "Great African World War"—these two countries were on opposite sides: Angola, as in the first war, supported those who "(re)formed" the DRC, while Rwanda, in the second war, was one of the opponents and invaders of the DRC. This dynamic created a regional instability that persists to this day.